Altered Structure-Function Coupling Associated with Attention Decline in Shift Work Disorder - Wu Z; Feng S; Li K; Dong L; Zhang L; Ning Y; Yin D (Nature and Science of Sleep)
Ziyao Wu,1,2,* Sitong Feng,1,2,* Kuangshi Li,3,* Linrui Dong,4 Liang Zhang,1,2 Yanzhe Ning,1,2 Dongqing Yin1,2 1Beijing Key Laboratory of Mental Disorders, National Clinical Research Center for Mental Disorders & National Center for Mental Disorders, Beijing Anding Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Advanced Innovation Center for Human Brain Protection, Capital Medical University, Beijing, People’s Republic of China; 3Department of Rehabilitation, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 4Fengtai Mental Health Center, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanzhe Ning, Beijing Key Laboratory of Mental Disorders, National Clinical Research Center for Mental Disorders & National Center for Mental Disorders, Beijing Anding Hospital, Capital Medical University, Beijing, People’s Republic of China, Email ningzy0923@mail.ccmu.edu.cn Dongqing Yin, Beijing Key Laboratory of Mental Disorders, National Clinical Research Center for Mental Disorders & National Center for Mental Disorders, Beijing Anding Hospital, Capital Medical University, Beijing, People’s Republic of China, Email yindq1123@mail.ccmu.edu.cnIntroduction: Previous studies on shift work disorder (SWD) have revealed altered functional and structural brain networks underlying attention decline. However, changes in structure-function coupling (SFC) and their relationship with attention decline remain unknown. This study aimed to examine the role of changed SFC in abnormal attentional network function in SWD.Methods: Thirty-four patients with SWD and thirty-two healthy controls were recruited. All participants underwent resting-state functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI) scans. All participants underwent an attentional network test to evaluate their functions. Finally, Pearson’s correlation analysis was conducted to analyze the association between aberrant attentional network function and altered structural and functional connectivity (SC-FC) coupling in patients with SWD.Results: Compared to healthy subjects, decreased alerting and executive functions were found in patients with SWD. In addition, we observed decreased SC-FC coupling in patients with SWD, specifically in the left anterior cingulate gyrus (T = − 3.6449, P = 0.0003), central opercular cortex (T = − 3.7187, P = 0.0002), middle frontal gyrus (T = − 3.8342, P = 0.0001), and parietal operculum cortex (T = − 3.6121, P = 0.0003), compared with healthy subjects. Better altering performance was significantly associated with lower SC-FC coupling in the anterior cingulate gyrus of patients with SWD (r = − 0.51, P = 0.002).Discussion: Our findings unravel that the decreased SC-FC coupling in the anterior cingulate gyrus may contribute to the impaired altering network function in SWD, which can further understand the neural mechanisms of impaired attention in SWD and inform a potentially therapeutic intervention for SWD patients.Keywords: shift work disorder, fMRI, attentional network function, structure-function coupling